Substituted naphthoquinones as novel amino acid sensitive reagents for the detection of latent fingermarks on paper surfaces - Jelly, R.; Lewis, Simon; Lennard, C.; Lim, K.; Almog, J. (Elsevier, 2010)
In this paper, we present our preliminary studies into naphthoquinones as novel reagents for the detection of latent fingermarks on paper. Latent fingermarks deposited on paper substrates were treated with solutions of selected naphthoquinones in ethyl acetate/HFE-7100, with subsequent heating. The selected compounds were 1,4-dihydroxy-2-naphthoic acid, 1,2-naphthoquinone- 4-sulfonate, 2-methoxy-1,4-naphthoquinone and 2-methyl-1,4-naphthoquinone. All of the tested compounds yielded purple-brown visible fingermarks, which also exhibited photoluminescence when illuminated with a high intensity filtered light source at 555nm and viewed through red goggles. Indirect heat using an oven at 150 C for1 h was found to be superior to direct heat with an iron, which while providing faster development lead to increased levels of background colouration. Luminescence spectrophotometry revealed differences in photoluminescence characteristics for fingermarks developed with the different naphthoquinones, with excitation over the range 530-590 nm. Luminescence spectrophotometry of developed lysine, glycine and serine spots on paper was used to confirm that the naphthoquinones were reacting with amino acids in the latent fingermark.